Network Security and Cryptography: Threats, Obstacles and Solutions - A Bibliometric Analysis - Singh, Purushottam; Dutta, Sandip; Pranav, Prashant (Recent Advances in Computer Science and Communications, 2025)
BackgroundIn the wake of escalating cyber threats and the indispensability of robust network security mechanisms, it becomes crucial to understand the evolving landscape of cryptographic research. Recognizing the significant contributions and discerning emerging trends can guide future strategies and technological advancements. Our study endeavors to shed light on this through a bibliometric analysis of publications in the realms of Network Security and Cryptography.MethodTo chronicle and synthesize the progression of research methodologies from their inception to the present day, we undertook a comprehensive Bibliometric Analysis of Network Security and Cryptography. Our data set was culled from the Clarivate Analytics Web of Science Database, encompassing 3,897 papers, 603 sources, and 7,886 authors from across the globe.ResultsOur analysis revealed a marked upsurge in cryptographic research since 1992, with China standing out as a dominant contributor in terms of publications. Notably, while 'security' and 'cryptography' emerged as recurrent research themes, there's an observable downtrend in international collaborations. Our study also highlights pivotal topics shaping the network security domain, offering insights into the trajectories of research source growth, structural variabilities in research relevance, and prospective intellectual and collaborative avenues as guided by authorship patterns.ConclusionCryptographic research is on an upward trajectory, both in volume and significance. However, the tapering of international collaborations and an evident need to concentrate on emergent challenges, such as data privacy and innovative network attacks, emerge as notable insights. This bibliometric review serves as a compass, directing researchers and academicians towards areas warranting heightened attention, thereby informing the roadmap for future investigative pursuits.
Keywords: cyber threats